Rotary LED Transmitter for Improving Data Transmission Rate of Image Sensor Communication - Shintaro Arai; Zhengqiang Tang; Akinori Nakayama; Haruhiro Takata; Tomohiro Yendo (IEEE Photonics Journal, 2021)
This study focuses on image sensor communication (ISC), which is a form of visible light communication, using a light-emitting diode (LED) and a camera as the transmitting and receiving device, respectively. In an ISC system, the receiver captures optical signals transmitted by blinking LEDs as an image and demodulates the data using the captured image. The ISC system can spatially separate signals and noises in the image, thus providing superior anti-interference ability. However, because the speed of ISC depends on the shooting speed of the camera, the receiver suffers from a low data transmission rate when a low-speed camera is used. To improve the data rate of ISC, we have developed a rotary LED transmitter. This transmitter cylindrically rotates the blinking LEDs during the exposure time of the camera. The camera captures multiple blinking states of LEDs as afterimages in a single image, thereby increasing the amount of data received per image. In this paper, we propose an ISC system using a rotary LED transmitter and present an experiment for the evaluation of the data rate. The result indicates that the data rate of the rotary LED transmitter is 60 times that of the conventional method.